Cultural diplomacy in Korean drama descendants of the sun / Nurshazani Mustafha and Fariza Hanis Abdul Razak - Mustafha, Nurshazani; Abdul Razak, Fariza Hanis (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2020)
'Korean wave' or better known as hallyu has been a phenomenon across the whole world, whether it is the United States, Latin America states, European countries, East Asia and even Southeast Asia countries. Ironically, these countries are generally having totally different cultures, languages, historical customs and some of the countries are having totally different political inclination from the state of South Korea. Yet, the Korean Wave hit the world so rapidly and consequently having a massive number of fans and followers regardless of race, religion and social status. Due to that reason, Korean Wave is not just seen as entertainment per se but it is also a tool and medium used by the state of Korea to influence and spread ideology, particularly culture, abroad. This research, focusing on the drama Descendants of the Sun, was seen as a tool for cultural diplomacy through its depiction of cultural elements in it. Therefore, this research involves two objectives: i) to identify cultural themes that are emerged in Korean drama, the Descendants of the Sun, and ii) to analyse the use of culture in Korean drama as part of Korea's cultural diplomacy. The method of video content analysis was employed in this study. The researcher observed in-depth all the 16 episodes of the drama series in order to achieve the objectives. In addition, coding sheets were also been used to assist in data collection. Therefore, the findings of the research include the emergence of 13 cultural elements in the drama Descendants of the Sun namely, i) obedience and respect, ii) seniority, heredity and authority, iii) order between ruler and subject, iv) punctuality, v) modest, vi) Korean traditional values, vii) Korean national branding, viii)patriotism, ix)discipline, x)relationship between parent and children, xi) power hierarchy, xii) motivation culture and xiii) diplomacy. The elements above basically respond as cultural diplomacy whenever the audiences (local and international) feel attached and influenced with it after watching the drama.